Ambiguity and uncertainty in mafia migrant settings: Social harms and intimate wounding by the ‘ndrangheta in Australia - Sergi, Anna (Journal of criminology, 2025)
In Australia, mafia-type families connected to the Calabrian ‘ndrangheta have been successful at exploiting criminal opportunities across generations and places. These families or dynasties have existed “down under” for decades; they have exploited the Calabrian diaspora while manipulating the rich cultural heritage that migrants had brought with them. While the economic harms connected to the presence of mafia-type groups and their activities are well known, empirically, what is less known are non-material harms that originate directly or indirectly from the proximity to such families, or the construction of their “threats”. Based on life history interviews in Australia, this article will explore unintended and hidden harms of the ‘ndrangheta in Australia: on the one hand, social harms, which amount to misrecognition of culture (cultural harm), stigmatisation, and social silencing. On the other hand, “intimate wounding”, which include indirect harms to people in proximity to mafia environments, such as autonomy and relational harms, as well as exposure to violence in ‘ndrangheta families. This paper will present a theoretical framework that contributes and complements both studies on mafia mobility and zemiology, by exploring the role of ambiguity and uncertainty in mafia migrant contexts.